La imagen del poder y el poder de la imagen. Alfonso X de Castilla y el infante don Felipe - Olga Pérez Monzón (Centre de Recherches sur les Mondes Américains, 2009)
Since Antiquity, the funeral of the most eminent people in society united a private ritual, characteristic of a family atmosphere, with another public ritual directed to the recognition of citizenship. The Middle Ages maintained a similar behavior in the cult of its illustrious dead and granted a important propagandistic dimension to the funeral procession. The funeral cortege was also understood like a public manifestation of respect to the deceased king and, by extension, to the elite of the kingdom. The funeral sculpture of gothic Castile chose this sequence as a frequent artistic subject. The tomb of the infant don Felipe (+1274) in Villalcázar de Sirga (Palencia) it is a case in point. This monument is known for its artistic value but, first of all for the political meaning of an iconography that represents the confrontationtowars the policy of affirmation of the monarchical power of his brother, the king Alfonso X the Wise.